PENERAPAN ELECTRONIC WORD OF MOUTH (eWOM) DAN PRINSIP KOMUNIKASI DALAM ISLAM - Rozi, M Fatkhur (IQTISHODUNA, 2017)
Abstract: This paper attempts to construct eWOM concepts based on input-process-output perspectivesthat produce a framework based on the identification of academic literature. This is based on the developmentof the internet world, e-commerce, and electronic word of mouth (eWOM) that is able to influence consumerbehavior. The approach of this paper uses the literature review method of several journals relevant to thetheme and study of communication principles in Islamic perspective and then discuss the data. The findingsin this paper suggest that eWOM is relatively new. This is considered to be quite representative in theliterature review regarding eWOM. The results of the review also get some research showing the theory thatexplains about eWOM phenomenon. The discussion not only aims to meet the gap in eWOM research butalso produces an overview in analyzing eWOM communication. It can present a structured approach inresearching various literatures and identify existing trends and gaps, aiming to find an overview in research oneWOM. The results can integrate the classification framework that can present the concept framework inother studies.